Health communication research performance in 2013-2022: a bibliometric analysis - Li, Qiong; Mohammad Razi, Siti Aishah; Mohd Zulkefli, Nor Afiah (Human Resource Management Academic Research Society, 2024)
Health communication is one of the crucial fields of contemporary research, especially in the post-Covid-19 epidemic era. In the last decade (2013-2022), however, no bibliometric performance analysis of the health communication (HC) overall has been conducted.To investigate research performance in HC, including performance of different countries/regions, institutions/groups, authors, journals, research areas, as well as status of collaboration and funding support. On January 25, 2023, a search for topic terms and article sources was carried out using Web of Science Core Collection. Then, duplicate data were removed, and a manual screening process was implemented. Bibliometric indicators were selected. Finally, data collection, analysis, and graph were performed using Excel 2019 and Origin 8.5.The quantity of publications in HC has steadily risen from 2013, and experienced rapid growth after 2019, whereas these publications’ overall impact has been on a decline. The articles are predominantly situated within the fields of social sciences, medicine, environmental science, and science and technology, for these areas benefit from the highest level of financial support. USA continues to hold an absolute leadership position in research productivity, reflected in the preponderance of prolific institutions and authors affiliated with USA. Additionally, among the top productive18 journals, half are OA, and importantly, their h-indices tend to be on par with non-OA journals. At last, collaboration between authors and institutions is widespread, however, the degree of international collaboration is relatively low. For HC research, diverse nations should strive to overcome cultural and political barriers, fostering stronger research collaborations. The diminishing influence of HC articles over the years may not be a reflection of a decline in scholarly quality; instead, it might be the integration of knowledge with substantial heterogeneity.